COVID-19: posibles efectos en la educación mastozoológica y otras disciplinas biológicas - Sosa-Escalante, Javier Enrique; Gallina, Sonia; Martínez-Meyer, Enrique; Cortés-Calva, Patricia; Mac Swiney G, M. Cristina; Iñiguez-Dávalos, Luis Ignacio; Gallo-Reynoso, Juan Pablo; Monroy-Gamboa, Alina Gabriela; Servin, Jorge; Sánchez-Rojas, Gerardo; et al. (THERYA, 2020)
....